Fabrication of Electrochemical Sensor Based on CeO2−SnO2 Nanocomposite Loaded on Pd Support for Determination of Nitrite at Trace Levels. Issue 5 (7th January 2020) - Mahmoodi, Aram; Ensafi, Ali A.; Rezaei, Behzad
Abstract: Here, an electrochemical sensor based on CeO2 ‐SnO2 /Pd was prepared and used for highly selective and sensitive determination of nitrite in some real samples. This nanocomposite was characterized by various methods like X‐ray photoelectron spectroscopy, X‐ray diffraction, energy dispersive spectroscopy, Fourier‐transform infrared spectroscopy, field emission scanning electron microscopy, and transmission electron microscopy. The electrochemical behavior of the sensor was evaluated by cyclic voltammetry. The results showed excellent catalytic property of the nanocomposite as a an electrocatalyst for nitrite oxidation. In the following, the experimental parameters affecting the analytical signal for nitrite were optimized. Under the optimal conditions, the limit of detection and sensitivity of the sensor were calculated as 0.10 μM and 652.95 μA.mM −1 .cm −2, respectively. Also, the response of the sensor was linear in the range of 0.36 to 2200 μM of nitrite. Finally, some of the inherent features of the sensor such as repeatability, reproducibility and stability were examined after evaluation of the sensor selectivity in the presence of several interfering species. Abstract :